A convenient and clean synthetic method for borasiloxanes by Pd-catalysed reaction of silanols with diborons. Issue 43 (12th May 2017) - Yoshimura, Aya; Yoshinaga, Michiyo; Yamashita, Hiroshi; Igarashi, Masayasu; Shimada, Shigeru; Sato, Kazuhiko
Abstract : Pd-Catalysed O -borylation of silanols with diborons selectively proceeded to give the corresponding boryl silyl ethers in high yields. Abstract : Selective O -borylation of silanols with diborons took place in the presence of Pd catalysts to give the corresponding boryl silyl ethers in high yields.